Clinical characteristics of family-clustered onset of coronavirus disease 2019 in Jilin Province, China. Issue 1 (1st January 2020) - Du, Na; Jiang, Yanfang; Zhang, Qing; Che, Lihe; Li, Xiaohua; Lou, Lixin; Bao, Wanguo; Hua, Shucheng
ABSTRACT: Eight members of a big family with laboratory-confirmed COVID-19 pneumonia were admitted to First Hospital of Jilin University, Changchun, China, from 28 January to 5 February 2020. The clinical records, laboratory results, and chest computed tomography (CT) scans were retrospectively reviewed. Throat swab samples were positive for severe acute respiratory syndrome coronavirus 2, confirmed by the Center for Disease Control and Prevention of Changchun. All eight patients had fever of different degrees; and 6, 3, and 2 had cough; diarrhea; and sore throat. With disease progression, the percentage of lymphocytes in older patients increased, CT images worsened, and the ratio of lymphocytes increased when images revealed inflammation absorption. Although the CT images showed ground-glass opacities in the youngest patient, his lymphocyte count did not decrease with mild clinical symptoms, and the images showed that inflammation was quickly absorbed. Only the oldest patient developed critical illness. The C reaction protein (CRP) levels of Patient 5 increased significantly, and the rate of decline was the slowest, while his condition was the most severe. The clinical manifestations of COVID-19 in this family cluster varied with contact, age, and underlying disease. Lymphocyte count and quality of chest CT images appeared inversely associated with disease severity. CRP changes may be an indicator of disease severity and prognosis.